Penurunan Berat Timbulan Sampah Buah Jeruk Mandarin (Citrus reticulata) Menggunakan Maggot Black Soldier Fly (Hermatia illucens) Tahun 2021:Studi Awal - Atang Saputra; Muhammad Akmal; Agus Riyanto; Budi Pramono (CV. Multi Kreasi Media, 2022)
Organic waste is an item that is no longer used or discarded by its owner, organic waste can be used or reprocessed into something useful. Organic waste is waste that can experience weathering or decomposition and breaks down into smaller materials. Organic waste at the Kramat Jati Main Market, East Jakarta, is disposed of directly and there is no prior sorting process, so the waste piles up. One of the methods for reducing the weight of waste generation is by using the maggot Black Soldier Fly medium. This study entitled